-9(y+3)=-7y-35

Simple and best practice solution for -9(y+3)=-7y-35 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9(y+3)=-7y-35 equation:



-9(y+3)=-7y-35
We move all terms to the left:
-9(y+3)-(-7y-35)=0
We multiply parentheses
-9y-(-7y-35)-27=0
We get rid of parentheses
-9y+7y+35-27=0
We add all the numbers together, and all the variables
-2y+8=0
We move all terms containing y to the left, all other terms to the right
-2y=-8
y=-8/-2
y=+4

You can always share this solution

See similar equations:

| 0.5x-1=-0.5x+7 | | –4w?8=–2w+8 | | 18a+9=10a+50 | | x=(715)(11) | | .5x-4=5.5 | | A=(6x+29)° | | C=1/2(1)(1+m) | | 2d+7+6d-30=0 | | .4x-4=2.4 | | 6+(8+6)=2a | | 125-20=x(8-2)+2x-3x | | x-12=0.7x | | d/5.4=2 | | 3x+5=20-(1/2x) | | 0=4+(x÷5) | | 2x=Y-15 | | 53?102=x(8?2)+2x?3x | | 3(x-)=-21+3x | | 9m-15m=24 | | 3y-5y+10y-4=0 | | 8x-15=5×+6 | | 5r-2=12 | | 3(x-8)+6x=0+3x | | b+11/3=3- | | (9x-5+10x-2)/2=27x+3 | | 2x/6-x/2=3(x-5) | | (27x+3+10x-2)/2=9x-5 | | -12+x11=0 | | 9x+11-7x-5=-20 | | 7x-11-4x+8=18 | | 0.5x=300 | | 4/8+2/5=4/7x |

Equations solver categories